A Coordinated Power Control Strategy for Urban Micro-Grid. (February 2019) - Luo, Xiao; Peng, Peng; Shao, Yuying; Li, Jian; Yu, Guoqin
Abstract: In modern urban energy system, micro-grid can be an effective solution to improve the power system reliability. However, power balance and voltage stability are everlasting issues in micro-grid. In this paper, a coordinated power control strategy based on demand response (DR) technology for urban micro-grid is introduced. The key components of this novel control scheme are the smart load (SL) controller of flexible load and the grid-tie inverter of renewable energy (RE) source. Both the SL controller and the dynamic grid-tie inverter are operated as series reactive power compensator (RPC), on one hand, the SL controller offers active power variation in the flexible load for energy storage capacity reduction, on the other hand, the dynamic grid-tie inverter of RE can regulate the out-put voltage of the inverter. Detailed mathematical derivations of the proposed control paradigm are provided. Results validate the effectiveness of adopting this coordinated power control scheme for an isolated urban micro-grid with renewable energy source and energy storage system.